SR-ND ISOTOPIC RECORD OF MULTI-STAGE INTERACTIONS BETWEEN MANTLE-DERIVED MAGMAS AND CRUSTAL COMPONENTS IN A COLLISION CONTEXT – THE ULTRAMAFIC-GRANITOID ASSOCIATION FROM VIVERO (HERCYNIAN BELT, NW SPAIN) - Galan G.; Pin C.; Duthou J.L. (My University, 1996)
Late-stage, epizonal calc-alkaline granitoids of the Hercynian belt are often associated with coeval more basic rocks. Such granitoids have been the focus of special attention when studying the role of mantle-derived magmas in granitoid genesis. These studies conclude that basic magmas are involved in granitoid production but their contribution to the chemical composition of granitoids is often controversial. The Vivero massif (NW Spain) includes calc-alkaline granitoids and coeval ultramafic and mafic rocks, but these granitoids are syntectonic and intruded into middle-crustal levels during an early stage.Scattered major- and trace-element chemistry together with heterogeneous Sr-Nd isotopic results preclude an origin of this ultramafic-to-granitoid association by any closed-system fractionation process. Ultramafic rocks include peridotites, pyroxenites and hornblendites with εNdi from -3.5 to -1.3 and (87Sr/86Sr)i ratio from 0.7059 to 0.7080. They are interpreted as cumulates formed by ''in situ'' fractional crystallization from contaminated basaltic magmas, particularly by interaction with 87Sr-enriched fluids. Mafic rocks comprise biotite-amphibole diorites, quartz diorites and tonalites with εNdi from -3.8 to 0.0 and (87Sr/86Sr)i ratio from 0.7058 to 0.7073. They represent either cumulates or more evolved magmas of calc-alkaline affinity. These rocks display an inverse correlation between the degree of differentiation and the degree of contamination inferred from isotope data. This points to wall-rock assimilation by thermal erosion during ascent of basic magmas up to the middle crust and supports the participation of mantle sources with positive εNdi and (87Sr/86Sr)i < 0.7058.Granitoids range from amphibole-biotite tonalites, through biotite granodiorites to monzonitic granites. They show an isotopic trend which diverges from that of ultramafic and mafic rocks. εNdi (-6.0 to -1.9) decreases while (87Sr/86Sr)i ratio (0.7061 to 0.7082) increases from tonalites to monzonitic granites, reflecting an increasing contribution of crustal components in more differentiated rocks. Assimilation and fractional crystallization, mixing included, account for such an evolution. Contamination of basic magmas by this process occurring at deeper crustal level produced hybrid tonalites and related mafic magmatic enclaves. Only monzonitic granites are interpreted as pure crustal melts. Their HREE fractionated patterns [(Gd/Yb)N = 4-5] suggest equilibrium with a garnet-rich residuum. Partial melting of moderate time-integrated Rb/Sr protolith, such as greywackes and/or meta-igneous rocks of intermediate-acid composition, could account for the isotopic composition of these monzogranites.This example shows that at least some calc-alkaline granitoids of collisional settings are not produced by pure intra-crustal melting. They are formed through a complex, multi-stage hybridization process, involving mantle-derived magmas, crustal components and several concomitant magmatic processes.